Perbandingan Hasil Peramalan Jumlah Kasus HIV Berdasarkan Jenis Kelamin di Kota Malang dengan Metode Exponential Smoothing - Afrian Eskartya Harjono; Kuntoro Kuntoro (Universitas Airlangga, 2017)
Human Immunodeficiency Virus or HIV is still one of the most serious problems especially in developing countries. This study used HIV cases that recorded in Health Departement of Malang City, East Java, as one of the variables to determine the forecasting results using Exponential Smoothing. Goals from this study was for showed the results of forecasting with Exponential smoothing method’s that hoped could be a consideration to HIV prevention’s program.This study was a non reactive research using secondary data of male and female HIV cases from January 2012 to December 2016 as a variable that would show the results of forecasting. The result of forecasting with single exponential smoothing method on parameter value α=0.5 for male HIV cases and α = 0.6 for female HIV cases. The accuracy value in this forecasting can be seen on MAPE value at parameter α = 0.5 is 27.87 for male HIV cases and parameter α = 0.6 is 47.06 for female HIV cases. The results of the forecast could be concluded that in 2017 the number of HIV cases in man and woman were totally increased from the last years, need to arrange a suitable programs that which aim to resolve the problem.